Women Micro And Small Business Sustainability In Malaysia Through Microcredit - Al-Shami, Samer Ali Hussein; Abdul Majid, Izaidin; Abdul Rashid, Nurulizwa; Abdul Raheem, Hayder Adil (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Micro and small enterprises sustainability. An explorative case study was conducted through semi interviews with 22 of women borrowers who received loan from Amanah Ikhtiar Malaysia (AIM) since three years in Selangor. We find that the majority of women who received loan three years ago have successfully operated their micro and small enterprises. However, they still suffer of sustainability and the majority of them still in the infant stage. There are many causes that affect the sustainability of women micro and small enterprises such as lack of product diversity and the inflexible of the implementation process of loan disbursement and repayment. Therefore, re-innovate AIM product as well as process is an important factor for women small business sustainability. In addition, control market competition and protect micro businesses is another important factor towards sustainability.